Ultra weak photon emission—a brief review - Mould, Rhys R.; Mackenzie, Alasdair M.; Kalampouka, Ifigeneia; Nunn, Alistair V. W.; Thomas, E. Louise; Bell, Jimmy D.; Botchway, Stanley W. (Frontiers in Physiology, 2024)
Cells emit light at ultra-low intensities: photons which are produced as by-products of cellular metabolism, distinct from other light emission processes such as delayed luminescence, bioluminescence, and chemiluminescence. The phenomenon is known by a large range of names, including, but not limited to, biophotons, biological autoluminescence, metabolic photon emission and ultraweak photon emission (UPE), the latter of which shall be used for the purposes of this review. It is worth noting that the photons when produced are neither ‘weak’ nor specifically biological in characteristics. Research of UPE has a long yet tattered past, historically hamstrung by a lack of technology sensitive enough to detect it. Today, as technology progresses rapidly, it is becoming easier to detect and image these photons, as well as to describe their function. In this brief review we will examine the history of UPE research, their proposed mechanism, possible biological role, the detection of the phenomenon, and the potential medical applications.